Composition and in vitro cytotoxic activities of essential oil of Hedychium spicatum from different geographical regions of western Himalaya by principal components analysis. Issue 10 (18th May 2016) - Mishra, Tripti; Pal, Mahesh; Meena, Sanjeev; Datta, Dipak; Dixit, Prateek; Kumar, Anil; Meena, Baleshwar; Rana, T.S.; Upreti, D.K.
Abstract : The rhizome of Hedychium spicatum has been widely used in traditional medicines. The present study deals with the evaluation of the cytotoxic potential of rhizome essential oils from four different regions of the Western Himalaya (India) along with comparative correlation analysis to characterise the bioactive cytotoxic component. The essential oils were coded as MHS-1, MHS-2, MHS-3 and MHS-4, and characterised using GC-FID and GC–MS. The main volatile compounds identified were 1, 8-cineol, eudesmol, cubenol, spathulenol and α-cadinol. In vitro cytotoxic activities were assessed against human cancer cell lines such as, the lung (A549), colon (DLD-1, SW 620), breast (MCF-7, MDA-MB-231), head and neck (FaDu), and cervix (HeLa). MHS-4 is significantly active in comparison to other samples against all cancer cell lines. Sample MHS-4 has major proportion of monoterpene alcohol mainly 1, 8-cineol. Principal components analysis was performed for the experimental results and all four samples were clustered according to their percentage inhibition at different doses. Abstract :